2016
DOI: 10.1016/j.biortech.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic co-digestion: A critical review of mathematical modelling for performance optimization

Abstract: Anaerobic co-digestion (AcoD) is a pragmatic approach to simultaneously manage organic wastes and produce renewable energy. This review demonstrates the need for improving AcoD modelling capacities to simulate the complex physicochemical and biochemical processes. Compared to mono-digestion, AcoD is more susceptible to process instability, as it operates at a higher organic loading and significant variation in substrate composition. Data corroborated here reveal that it is essential to model the transient vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
100
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(110 citation statements)
references
References 99 publications
0
100
0
10
Order By: Relevance
“…Hashimoto used straw as a carbon source along with poultry waste. Having information on the C/N ratio of available materials in the region, a suitable mixture of wastes, can be selected to feed the biogas plant [31]. According to the literature [28,30,31], the entry of the substances into the digestive process would be a proportion of the poultry feces, the straw, and the cow feces, which would allow the C/N ratio in the digestive solution to be adjusted at an ideal ratio.…”
Section: Required Raw Materialsmentioning
confidence: 99%
“…Hashimoto used straw as a carbon source along with poultry waste. Having information on the C/N ratio of available materials in the region, a suitable mixture of wastes, can be selected to feed the biogas plant [31]. According to the literature [28,30,31], the entry of the substances into the digestive process would be a proportion of the poultry feces, the straw, and the cow feces, which would allow the C/N ratio in the digestive solution to be adjusted at an ideal ratio.…”
Section: Required Raw Materialsmentioning
confidence: 99%
“…To further enhance energy production via AD, co-digestion of WAS and other organic feedstocks (e.g. food waste) has been investigated (Xie et al, 2016;Yin et al, 2016). In this co-digestion process, food waste rich in organics was directly fed into the anaerobic digester with WAS to promote the biogas production.…”
Section: Energy Recoverymentioning
confidence: 99%
“…This study demonstrated that net power production was an appropriate measure to optimize feedstock ratio of co-digestion under three different mixing conditions. (Xie, 2016). In another study, full scale digesters maintained stability under overloaded low mixing conditions.…”
mentioning
confidence: 93%
“…In another study, full scale digesters maintained stability under overloaded low mixing conditions. To achieve similar fluid properties of the digestate, an increase in mixing intensity is needed based on varying amounts and types of co-substrates (food wastes) (Xie, 2016). To understand the relationship between mixing and methane yield, two-stage computational simulations should account for biological processes with steady fluid flow and heat transfer.…”
mentioning
confidence: 99%